Karakteristik Pati Buah Mangrove Bruguiera gymnorrhiza Dan Sonneratia caseolaris Berpotensi Sebagai Edible Film Dari Kawasan Perairan Gorontalo Utara - Frezky Arismunandar Pakaya; Rita Marsuci Harmain; Rahim Husain (Jambura Fish Processing Journal, 2026)
The mangrove fruit species Bruguiera gymnorhiza and Sonneratia caseolaris have potential as an edible films for optimizing local natural resources and supporting the food packaging industry. The objective of this study was to characterize the chemical properties of the starch from the mangrove fruits of B. gymnorhiza and S. caseolaris and to compare the chemical characteristics of the starch from these two species to determine which has greater potential as an edible film from the waters of North Gorontalo. The research method employed a completely randomized experimental design with two replicates, analyzed using Analysis of Variance (ANOVA) and a post-hoc t-test. The selection of the preferred product was determined using a t-test. Test parameters included moisture content, total starch, amylose, and amylopectin in the mangrove fruits of B. gymnorhiza and S. caseolaris, respectively. The results showed that the moisture content of B. gymnorhiza mangrove fruit flour was 8.53%, while that of S. caseolaris was 8.14%. The total starch content in B. gymnorhiza mangrove fruit was 32.27%, while that in S. caseolaris was 21.43%. The amylose content in B. gymnorhiza mangrove fruit was 26.96%, and the amylopectin content was 5.31%. In S. caseolaris mangrove fruit, the amylose content is 18.45% and the amylopectin content is 2.98%. B. gymnorhiza mangrove fruit flour has greater potential for use as an edible film because it has a higher total starch content compared to S. caseolaris mangrove fruit flour.